Charge-spin conversion in layered semimetal TaTe_{2} and spin injection in van der Waals heterostructures - Anamul Md. Hoque; Dmitrii Khokhriakov; Bogdan Karpiak; Saroj P. Dash (Physical Review Research, 2020)
A spin-polarized current source using nonmagnetic layered materials is promising for next-generation all-electrical spintronic science and technology. Here we electrically created spin polarization in a layered semimetal TaTe_{2} via the charge-spin conversion process. Using a hybrid device of TaTe_{2} in a van der Waals heterostructure with graphene, the spin polarization in TaTe_{2} is efficiently injected and detected by nonlocal spin-switch, Hanle spin precession, and inverse spin Hall effect measurements. Systematic experiments at different bias currents and gate voltages in a vertical geometry prove the TaTe_{2} as a nonmagnetic spin source at room temperature. These findings demonstrate the possibility of making an all-electrical spintronic device in a two-dimensional van der Waals heterostructure, which can be essential building blocks in energy-efficient spin-orbit technology.